Segmentasi Jalan Berlubang Citra Jalan Raya Menggunakan Metode Thresholding Dan K-Means - Linda Sukmawati; Rifki Sadikin (Universitas Bina Sarana Informatika, 2023)
Abstract - One of the important meanings for human life is the road. The road is used as a means of transportation which has very useful planning in the development of human life. In 2018, based on statistical data, the number of motor vehicle users in Indonesia is increasing every year, reaching 146,858,759 units. Seeing the number of the enhancement of motor vehicle users, the impact occured. Many roads are damaged and the conditions are very unsettling and concerned for the road users. One of the most common damages is that there are many holes in the road, which can increase the accidents’ risk. Based on science and technology development, one of the causes for the lengthy time to repair road damage is due to calculating the area of each damage manually and it takes a relatively long time. For this reason, this study aims to perform image processing in the form of segmentation on the image of a potholed road on the highway using the Thresholding algorithm and K-Means, followed by the calculation of the area and perimeter of the hole. The results of this study were obtained with 106 images of potholed roads, then segmented and calculated the area and circumference can be read properly using a program that has been designed. Keywords: Segmentation, Thresholding, K-Means